2018
DOI: 10.5830/cvja-2017-031
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diastolic function after recovery from pre-eclampsia

Abstract: SummaryBackgroundPre-eclampsia is associated with significant changes to the cardiovascular system during pregnancy. Eccentric and concentric remodelling of the left ventricle occurs, resulting in impaired contractility and diastolic dysfunction. It is unclear whether these structural and functional changes resolve completely after delivery.AimsThe objective of the study was to determine cardiac diastolic function at delivery and one year post-partum in women with severe pre-eclampsia, and to determine possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…In our meta-analysis, BMI (19,(21)(22)(23)25,26,29,31,32) showed statistical significance (pp0.0001), consistent with recent findings (3,32) reporting a two-fold increase in the risk of diabetes in women with PE, as well as increased hypertension and serum glucose and lipid levels. Total cholesterol (21,23,25,29,31,32) and LDL (21,23,25,29,31,32) concentrations were higher in the control group, although the differences were not statistically significant.…”
Section: ' Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our meta-analysis, BMI (19,(21)(22)(23)25,26,29,31,32) showed statistical significance (pp0.0001), consistent with recent findings (3,32) reporting a two-fold increase in the risk of diabetes in women with PE, as well as increased hypertension and serum glucose and lipid levels. Total cholesterol (21,23,25,29,31,32) and LDL (21,23,25,29,31,32) concentrations were higher in the control group, although the differences were not statistically significant.…”
Section: ' Discussionsupporting
confidence: 92%
“…Our meta-analysis identified the following six significant and consistent factors among PE patients: higher SBP (19,(21)(22)(23)25,26,29), higher DBP (19,(21)(22)(23)25,26,29), higher blood insulin value, which is indicative of future diabetes development (21,23,25,29); and higher HDL, LDL, and insulin levels. These results agree in part with those in recent literature, including the meta-analyses by de Groot et al 35) used another approach comparing the quality of assessment and accuracy and specificity in women with PE and other hypertensive diseases in pregnancy.…”
Section: ' Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, moderate-severe left ventricular (LV) dysfunction and remodeling (according to the EAE/ASE diagnosis and grading of abnormal LV structure and function) were significantly more prevalent in formerly preterm PE women compared with those who had term preeclampsia and controls (3,6). Similarly, Soma-Pillay et al showed that women with early onset PE had an increased risk of diastolic dysfunction at 1 year post-partum (RR 3.41, 95% CI: 1.11-10.5, p = 0.04) and regardless of the presence of chronic hypertension (56). Breetveld et al in their prospective longitudinal cohort study confirmed that the prevalence of HF-B was consistently high (1 in 4) amongst formerly PE women at 1 and 4 years postpartum (41).…”
Section: Asymptomatic Heart Failurementioning
confidence: 88%
“…It leads to remodeling of the left ventricle and impaired contractility, resulting in diastolic dysfunction. Pre-eclampsia and other hypertensive disorders are known to be one of the five leading causes of maternal death worldwide and Pre-eclampsia increases the risk of future hypertension, ischemic heart disease, venous thromboembolism, and stroke [11]. We also known that it preserved the systolic function of the left ventricle in cases of preeclampsia, no matter how severe it is [12].…”
Section: Discussionmentioning
confidence: 99%